Pengaruh Kompetensi Profesional Guru Dan Motivasi Belajar Peserta Didik Terhadap Hasil Belajar Sejarah Kebudayaan Islam : Studi Kasus Kelas X MA Al Mahrusiyah - Husni Thoyyar; Zaenal Arifin; Ali Imron (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Teacher professional competence and student learning motivation are important factors influencing learning outcomes. However, some students still do not achieve the Minimum Completion Criteria (KKM), indicating the need for further investigation. This study aims to analyze the effect of teacher professional competence and student learning motivation on learning outcomes in Islamic Cultural History (SKI) among class X students at MA Al Mahrusiyah Lirboyo. This research employed a quantitative approach with a survey design. The population consisted of 279 students, with a sample of 74 selected using proportional random sampling. Data were collected through questionnaires and documentation, and analyzed using multiple linear regression. The results show that teacher professional competence significantly influences learning outcomes (R² = 0.710; sig. 0.001), as does student learning motivation (R² = 0.676; sig. 0.001). Simultaneously, both variables significantly affect learning outcomes (R² = 0.747; sig. 0.002). In conclusion, both partially and simultaneously, teacher professional competence and student learning motivation have a significant effect on students’ learning outcomes